POLIGAMI TANPA TRANSPARANSI DALAM TEORI BATAS MUHAMMAD SYAHRUR: STUDI FENOMENA VIRAL 2025 - Iefah Muflihah; Ardan Alfariz; Muhamad Farrij Hasbullah; Andi Rosa (JUTEQ: JURNAL TEOLOGI & TAFSIR, 2026)
This study examines the phenomenon of non-transparent polygamy that went viral in Indonesia in 2025 through the lens of Muhammad Syahrur’s Theory of Limits (Nazhariyyat al-Ḥudūd). The issue sparked extensive public debate regarding marital ethics, honesty, and the moral boundaries that govern contemporary polygamous practices. This research employs a qualitative library-based method, utilizing intra-textual analysis of Qur’anic verses alongside a review of Syahrur’s major works. Social data from the viral polygamy incident are incorporated to contextualize the ethical problems arising from the lack of transparency in modern practices. The findings reveal that, according to Syahrur, polygamy is not an absolute male right but a morally restricted action governed by minimum and maximum limits designed to ensure justice and protect women. Non-transparent polygamy violates the minimum threshold of justice by depriving women of accurate information, damaging trust, and causing psychological and social harm. Within the framework of the Theory of Limits, such practice constitutes an act of injustice (ẓulm) and contradicts the higher objectives of the Sharia (maqāṣid al-sharī‘ah). This study concludes that Syahrur’s Theory of Limits is highly relevant as an ethical paradigm for assessing modern polygamy. Polygamy can only be justified when practiced within strict moral boundaries that uphold transparency, honesty, and justice as essential principles of Muslim family life.